Prevalence of Depression and Associated Factors among Adults in Saudi Arabia: Systematic Review and Meta-Analysis (2000-2022) - Nour, Mohamed O.; Alharbi, Khulud K.; Hafiz, Tamara Abdulrahman; Alshehri, Ali M.; Alyamani, Lujain Sami; Alharbi, Taif Hazzaa; Alzahrani, Reuof Saleh; Almalki, Ebtehal Fawwaz; Althagafi, Asayel Atiah; Kattan, Ebtesam Tariq; Tamim, Hala Mamun (Depression and Anxiety, 2023)
Introduction. Depressive disorders are the leading causes of disability and disease burden worldwide. They were ranked fifth among the top causes of death and disability in Saudi Arabia, with subsequent impacts on productivity and economics when affecting adults. Objectives. The study aimed to systematically investigate the prevalence of depression and its associated factors among Saudi adults during 2000-2022. Methods. A systematic review and meta-analysis were conducted in accordance with the PRISMA guidelines using Medline/PubMed, ResearchGate, Google Scholar, and Ovid databases during 2000-2022 with predetermined inclusion and exclusion criteria. The quality of the included papers was determined, and heterogeneity between studies was assessed using the Q statistic to estimate the I2 value. A random effects model was used to drive the pooled depression prevalence with 95% confidence intervals (CI). A forest plot was generated to show estimates for individual studies. Publication bias was assessed visually with the funnel plots symmetry and Egger’s test (p<0.05). A sensitivity analysis was conducted to explore the effect of individual studies on the overall prevalence estimate. A subgroup analysis by the study, population characteristics, and depression tools were also run. Results. Forty-six cross-sectional relevant studies were identified, including 25814 participants. The pooled depression prevalence was 37.35% (95% CI: 33.61–41.98%) with high heterogeneity (I2=94.8%, p<0.001). In the subgroup analysis, the prevalence estimates were higher among females (34.5%), the singles (49.5%), undergraduate university students in university settings (47.7%), northern region (62.3%), and studies that utilized the Center for Epidemiological Studies-Depression (CES-D) scale (58.8%). Among the risk factors significantly associated with depression were female gender, being single, low education level, financial problems, poor housing condition, having medical problems, sleep disorders, presence of psychiatric/psychological conditions, life events, lack of social support, exposure to stress, educational/personal problems, and smartphone addiction. Conclusion. Almost more than one-third of Saudi adults had depression. Appropriate surveillance, early interventions, and depression management strategies are needed to decrease the prevalence and its consequences among adults.